2020
DOI: 10.3928/01477447-20200428-01
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Consumption and Time to Return to Work After Percutaneous Osteotomy in Foot Surgery

Abstract: Surgeries involving the foot and ankle are painful procedures, with many patients unwilling to discontinue prescribed narcotics at 3 months postoperatively. Percutaneous techniques allow for smaller incisions and minimal soft tissue disruption. Fifty consecutive patients underwent outpatient percutaneous foot surgery. Data were collected on pain medication taken and time to return to work. A mean of 3.3 tablets of oxycodone were consumed during the first 2 weeks. No patient was taking narcotics after 2 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…31 Although the latter study sets a good foundation for understanding narcotic consumption after HV correction, it does not look specifically at minimally invasive HV corrective surgery. Recently, Chan et al 6 showed that patients undergoing percutaneous foot and ankle surgeries consumed a mean of 3.3 tablets of oxycodone during the first 2 weeks, whereas no patients were taking narcotics after that time point. In their study, percutaneous surgery led to a significant reduction in postoperative narcotic consumption when compared to the reported values with open procedures.…”
Section: Discussionmentioning
confidence: 99%
“…31 Although the latter study sets a good foundation for understanding narcotic consumption after HV correction, it does not look specifically at minimally invasive HV corrective surgery. Recently, Chan et al 6 showed that patients undergoing percutaneous foot and ankle surgeries consumed a mean of 3.3 tablets of oxycodone during the first 2 weeks, whereas no patients were taking narcotics after that time point. In their study, percutaneous surgery led to a significant reduction in postoperative narcotic consumption when compared to the reported values with open procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing opioids for acute pain management in foot and ankle surgery is highly varied and without formal recommendation. The literature has few guidelines for opioid-prescribing practices, with only anecdotal suggestions offered, and because physicians cannot accurately predict how much analgesia a patient will require, opioids tend to be overprescribed [ 9 , 10 , 15 , 23 , 29 – 31 ]. Similarly, this study had a lack of a definitive consensus on prescribing opioid analgesics for moderate acute postoperative pain, however, the consensus to use opioids at more severe pain levels in this study is reflective of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this study had a lack of a definitive consensus on prescribing opioid analgesics for moderate acute postoperative pain, however, the consensus to use opioids at more severe pain levels in this study is reflective of the literature. These include a level II prospective observational cohort study that proposed patients who had hindfoot, ankle, or osseous procedures required more opioids [ 9 ], as well as the study by Chan et al that found fewer opioids were required postoperatively for percutaneous foot and ankle surgery due to the smaller incisions and minimal disruption to surrounding soft tissue [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced soft tissue damage may allow faster recovery and reduced postoperative pain. 3,31 Moreover, although the risk of sural nerve damage may be reduced by the percutaneous approach, it is important to place the skin incision with a beaver blade in a safe zone far from the nerve course, spreading deeper soft tissues with a smooth instrument (eg, a mosquito clamp) before using the Shannon burr. 6,16,33 Fluoroscopy can be helpful to reduce the learning curve, as reported on forefoot percutaneous techniques.…”
Section: Discussionmentioning
confidence: 99%